2011
DOI: 10.1053/j.gastro.2011.04.045
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Intake and Nutritional Deficiencies in Patients With Diabetic or Idiopathic Gastroparesis

Abstract: Background & Aims Gastroparesis can lead to food aversion, poor oral intake, and subsequent malnutrition. We characterized dietary intake and nutritional deficiencies in patients with diabetic and idiopathic gastroparesis. Methods Patients with gastroparesis on oral intake (n=305) were enrolled in the NIDDK Gastroparesis Registry and completed diet questionnaires at 7 centers. Medical history, gastroparesis symptoms, answers to a block food frequency questionnaire, and gastric emptying scintigraphy results w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
106
0
10

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(116 citation statements)
references
References 25 publications
(40 reference statements)
0
106
0
10
Order By: Relevance
“…Upper GI symptoms are usually exacerbated with eating, causing many patients to avoid food, leading to the onset of nutritional deficiencies. 4 Anorexia patients with a low body mass index (15 ± 2), indicative of substantial decrease in eating, reportedly experience impairment in olfaction. 12 Nutritional deficiencies, particularly proteins, decreases the ability of the GI epithelium to regenerate, which has been speculated to also affect the regeneration of olfactory epithelium, potentially serving as a cause of the smell dysfunction seen in malnourished anorexia patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Upper GI symptoms are usually exacerbated with eating, causing many patients to avoid food, leading to the onset of nutritional deficiencies. 4 Anorexia patients with a low body mass index (15 ± 2), indicative of substantial decrease in eating, reportedly experience impairment in olfaction. 12 Nutritional deficiencies, particularly proteins, decreases the ability of the GI epithelium to regenerate, which has been speculated to also affect the regeneration of olfactory epithelium, potentially serving as a cause of the smell dysfunction seen in malnourished anorexia patients.…”
Section: Discussionmentioning
confidence: 99%
“…3 Patients with both gastroparesis and GERD are advised to manage symptoms by eating less fats and decreasing the frequency and size of meals. 4 From experience in practice, it has been observed that some patients with gastroparesis and with GERD attribute decreased enjoyment when eating to changes in taste and smell function. However, no prior studies have identified taste and smell abnormalities in these upper GI disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Los síntomas más habituales son las náuseas (37). La prueba "gold standard" para su diagnóstico es la gammagrafía de vaciamiento gástrico (38). Los pacientes con gastroparesia diabética son más susceptibles a sufrir un deterioro del estado nutricional y, en nuestro paciente, además, un deterioro de su ERC.…”
Section: Peso Ajustado = [(Peso Real -Peso Ideal)] X 025 + Peso Idealunclassified
“…Los pacientes con gastroparesia diabética son más susceptibles a sufrir un deterioro del estado nutricional y, en nuestro paciente, además, un deterioro de su ERC. El manejo de la gastroparesia diabética inicialmente debe incluir (38):…”
Section: Peso Ajustado = [(Peso Real -Peso Ideal)] X 025 + Peso Idealunclassified
“…The support of a dietitian increases the chances that the diet will have a nutrient intake that reaches the daily energy requirements. Indeed, there appears to be a great need for this support since most patients experience difficulties following dietary advice [5]. In general, in terms of symptom-relief, a meal with small particle size seems to be of central importance [6].…”
Section: Gastroparesis Dietary Treatmentmentioning
confidence: 99%